把分式方程的两边同时乘以(x-2), 约去分母.得( ) A.1-=1 C.1-(1-x)=x-2 D.1+(1-x)=x-2 【
查看更多】
题目列表(包括答案和解析)
把分式方程
![](http://thumb.zyjl.cn/pic6/res/czsx/web/STSource/20131103201900855450205/SYS201311032019008554502006_ST/0.png)
的两边同时乘以(x-2),约去分母,得( )
A.1-(1-x)=1
B.1+(1-x)=1
C.1-(1-x)=x-2
D.1+(1-x)=x-2
查看答案和解析>>
把分式方程
![](http://thumb.zyjl.cn/pic6/res/czsx/web/STSource/20131101193227965279887/SYS201311011932279652798008_ST/0.png)
的两边同时乘以(x-2),约去分母,得( )
A.1-(1-x)=1
B.1+(1-x)=1
C.1-(1-x)=x-2
D.1+(1-x)=x-2
查看答案和解析>>
把分式方程
![](http://thumb.zyjl.cn/pic6/res/czsx/web/STSource/20131101190726524541977/SYS201311011907265245419007_ST/0.png)
的两边同时乘以(x-2),约去分母,得( )
A.1-(1-x)=1
B.1+(1-x)=1
C.1-(1-x)=x-2
D.1+(1-x)=x-2
查看答案和解析>>
把分式方程
![](http://thumb.zyjl.cn/pic6/res/czsx/web/STSource/20131101185759095831615/SYS201311011857590958316012_ST/0.png)
的两边同时乘以(x-2),约去分母,得( )
A.1-(1-x)=1
B.1+(1-x)=1
C.1-(1-x)=x-2
D.1+(1-x)=x-2
查看答案和解析>>